The effect of dexmedetomidine on liver injury secondary to lower extremity ischemia-reperfusion in a diabetic rat model - Seyfi Kartal; Ahmet Şen; Levent Tümkaya; Basar Erdivanlı; Tolga Mercantepe; Adnan Yılmaz (Clinical and Experimental Hypertension, 2021)
Introduction: In this study, we aimed to evaluate the hepatic protective effects of dexmedetomidine in the lower extremity ischemia-reperfusion model in diabetic rats biochemically and histopathologically. Methods: Rats were randomly divided into 4 equal groups (n = 6); Control (C) group, diabetic control group (DM), diabetic ischemia-reperfusion group (IR), group with diabetic IR and dexmedetomidine (DEX). In the IR and DEX groups were performed 120 min reperfusion after 120 min ischemia. In group DEX, 100 µ / kg dexmedetomidine was administered intraperitoneally 30 minutes before renal IR administration. Then, various histopathological and biochemical parameters were evaluated in liver tissue. Results: After ischemia-reperfusion, aspartate amino transaminase, alanine amino transaminase, total oxidant level, and thiobarbituric acid -reactive substances were increased, total thiol group and total antioxidant level were decreased and these parameters were found to improve in the group given dexmedetomidine. It was also observed that there was histopathological deterioration after ischemia-reperfusion and histopathological deterioration was found to be less with dexmedetomidine administration. Conclusion: The effects of lower extremity ischemia-reperfusion on hepatic tissue as distant organs were evaluated in diabetic rats, histopathologically, immunologically, biochemically, and liver damage was determined after ischemia-reperfusion, and dexmedetomidine was found to decrease liver damage.